Dendritic poly(benzyl ether)‐b‐poly(N‐vinylcaprolactam) block copolymers: Self‐organization in aqueous media, thermoresponsiveness and biocompatibility. Issue 3 (2nd November 2017) - Tang, Gang; Hu, Minqi; He, Fuxi; You, Dan; Qian, Yangyang; Bi, Yunmei
ABSTRACT: Four generations of new amphiphilic thermoresponsive linear‐dendritic block copolymers (LDBCs) with a linear poly( N ‐vinylcaprolactam) (PNVCL) block and a dendritic poly(benzyl ether) block are synthesized by atom transfer radical polymerization (ATRP) of N ‐vinylcaprolactam (NVCL) using dendritic poly(benzyl ether) chlorides as initiators. The copolymers have been characterized by 1 H NMR, FTIR, and GPC showing controlled molecular weight and narrow molecular weight distribution (PDI ≤ 1.25). Their self‐organization in aqueous media and thermoresponsive property are highly dependent on the generation of dendritic poly(benzyl ether) block. It is observed for the LDBCs that the self‐assembled morphology changes from irregularly spherical micelles, vesicles, rod‐like large compound vesicles (LCVs), to the coexistence of spherical micelles and rod‐like LCVs, as the generation of the dendritic poly(benzyl ether) increases. The results of a cytotoxicity study using an MTT assay method with L929 cells show that the LDBCs are biocompatible. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 300–308 Abstract : Novel amphiphilic thermoresponsive linear‐dendritic block copolymers composed of a linear poly( N ‐vinylcaprolactam) (PNVCL) chain and the first to the fourth generations of a Fréchet‐type polyether have been synthesized. Their self‐assembly behavior and thermoresponsive property are affected by the generation of the dendritic poly(benzyl ethers) block. They are proven to be nontoxic to L929 cells.